Diversity of arthropods associated with sheep, cow, goat, and camel manure in the southeast of Algeria - BENCHENNA, Mohammed Ben Yahia; DEHLIZ-LAKHDARI, Wassima; GUEZOUL, Omar; MARNICHE, Faiza; DEHLIZ, Abderrahmène (Studia Universitatis Babeș-Bolyai Biologia, 2025)
Within the region of southeast Algeria, the Berlese method was utilized to conduct an inventory of the arthropods that were associated with four different types of manure: cow, sheep, goat, and camel. A total of 6,908 arthropods were collected, and they were categorized into four classes, 14 orders, and 37 families. The three families, Histeridae, Sphaeroceridae, and Staphylinidae, were found almost everywhere, with the relative abundance of each family varying according to the type of manure. The Anthicidae and Scarabaeidae families, which are the only two families remaining, were distributed selectively. The Shannon diversity index (H’) for arthropod families obtained from the various types of manure reveals that sheep and goat manure display the highest level of diversity by (H’ = 2.26 bits) and (H’ = 2.23 bits), respectively. The frequency of the larval form (86.58%, NI = 5,981) compared to the adult form (13.42%, NI = 927) suggests that manure is an appropriate environment for incubating the immature stages of several arthropods. On occasion, members of certain families of pests were discovered. These families include Bostrychidae, Dermestidae, and Gryllotalpidae. Article history: Received 02 August 2024; Revised 15 April 2025; Accepted 26 May 2025; Available online 25 June 2025